Infostorms How to Take Information Punches and Save Democracy - Hendricks, Vincent F. (Springer International Publishing, 2014)
This detailed guide to navigating the bewildering superabundance of information in today's globalizing world draws on the latest work in philosophy and the social sciences to explore how information, and its misuse, can both support and undermine democracy
Description based on publisher supplied metadata and other sources
Keywords: Philosophie; Politik; Politische Wissenschaft; Information technology -- Philosophy; Information technology -- Political aspects; Political science -- Philosophy